Improved Efficiency of Microcrystalline Silicon Thin-Film Solar Cells With Wide Bandgap CdS Buffer Layer - Maria Jabeen; Shyqyri Haxha; Martin D. B. Charlton (IEEE Photonics Journal, 2017)
In this paper, we have reported a new structure based upon an optical simulation of maximum light trapping and management in microcrystalline silicon thin-film solar cells by using multitexture schemes and introducing an n-type cadmium sulphide (CdS) buffer layer with the goal of extreme light coupling and absorption in silicon absorber layer. Photon absorption was improved by optimizing the front and back texturing of transparent conductive oxide layers and variation in buffer layer thickness. We have demonstrated that light trapping can be improved with the proposed geometry of 1-μm-thick crystalline silicon absorber layer below a thin layer of wide bandgap material. We have improved the short-circuit current densities by 1.35 mA/cm2 resulting in a total short-circuit current of 25 mA/cm2 and conversion efficiency of 9% with the addition of CdS buffer layer and multitextures, under global AM1.5 conditions. In this study, we have used a two-dimensional full-vectorial finite element to design and optimize the proposed light propagation in solar cell structure configuration. Our simulation results show that interface morphology of CdS layer thickness and textures with different aspect and ratios have the most prominent influence on solar cell performance in terms of both short-circuit current and quantum efficiency.